2005
DOI: 10.1016/j.str.2005.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Induced Conformational Changes in Bacillus subtilis Glutamate Racemase and Their Implications for Drug Discovery

Abstract: D-glutamate is an essential building block of the peptidoglycan layer in bacterial cell walls and can be synthesized from L-glutamate by glutamate racemase (RacE). The structure of a complex of B. subtilis RacE with D-glutamate reveals that the glutamate is buried in a deep pocket, whose formation at the interface of the enzyme's two domains involves a large-scale conformational rearrangement. These domains are related by pseudo-2-fold symmetry, which superimposes the two catalytic cysteine residues, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
102
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(110 citation statements)
references
References 31 publications
7
102
1
Order By: Relevance
“…Therefore, at neutral pH, the cysteines exist as a rapidly equilibrating thiolate-thiol pair in the presence of the substrate. Indeed, no basic residue available for deprotonation of the thiol is present in the active site, in contrast to the recently reported structures of glutamate racemase from B. subtilis with D-glutamate (19) and of proline racemase from T. cruzi with pyrrole-2-carboxylic acid (20).…”
Section: Concomitant Orientation Of the Carboxylate To Maximize Orbitmentioning
confidence: 57%
See 3 more Smart Citations
“…Therefore, at neutral pH, the cysteines exist as a rapidly equilibrating thiolate-thiol pair in the presence of the substrate. Indeed, no basic residue available for deprotonation of the thiol is present in the active site, in contrast to the recently reported structures of glutamate racemase from B. subtilis with D-glutamate (19) and of proline racemase from T. cruzi with pyrrole-2-carboxylic acid (20).…”
Section: Concomitant Orientation Of the Carboxylate To Maximize Orbitmentioning
confidence: 57%
“…However, the ␣͞␤ domains of DAP epimerase (composed of mainly ␤-strands) are very different from those of aspartate racemase and glutamate racemase. A recent report on the crystal structure of glutamate racemase from B. subtilis in complex with D-glutamate reveals a similar conformational rearrangement in the enzyme upon substrate binding (19). Interestingly, despite the enzyme being cocrystallized in the presence of L-glutamate, the product D-glutamate was the species trapped in the crystal structure.…”
Section: Concomitant Orientation Of the Carboxylate To Maximize Orbitmentioning
confidence: 90%
See 2 more Smart Citations
“…5.1.1.3), which catalyzes the reversible stereoinversion of L-glutamate (5,14,31). Insights into the cofactor-independent amino acid racemases have begun to emerge from biochemical studies of enzymes isolated from several organisms, including Bacillus subtilis, Bacillus pumilus, Bacillus sphaericus, Escherichia coli, Lactobacillus fermentum, Lactobacillus brevis, Aquifex pyrophilus, Staphylococcus haemolyticus, Brevibacterium lactofermentum, and Mycobacterium tuberculosis (1,2,5,10,14,18,19,21,28,29,33,35,40,47,58,61), as well as the recently described crystal structure of RacE-D-glutamate from B. subtilis (43). Several studies have identified glutamate racemase as an essential gene in B. subtilis and E. coli, which has led to the prediction that glutamate racemase activity is important for peptidoglycan biosynthesis in these organisms (14,31).…”
mentioning
confidence: 99%